EVALUASI KEBISINGAN LALU LINTAS AKIBAT PENGARUH KEKASARAN PERMUKAAN JALAN PADA PERKERASAN KAKU DI JALAN TOL PADALARANG - CILEUNYI - Edward S. , Johannes
Road traffic noise affects environment. Two main causes of road traffic noise are noise come from vehicle engine and noise resulted from vehicle tire road surface interaction. Samuel (1982), determined that the most important factor propagates tire road noise from vehicles when its speed is above 40 kilo meter per hour, is road surface texture. In this research, the effect of a road surface texture, specifically roughness, on road traffic noise is also studied. Speed and Sound Pressure Levels (SPL) of 3 types of vehicles (car, truck 2 axles, truck with more 2 axles) on 3 types of roughness (IRI 1,93; IRI 2,25: IRI 2,76) are observed at 5 m and 10 m from the centreline of the road lane. The results showed that analysis of variance indicates that the traffic noise resulting from truck with two axles or more is significantly different among locations, whereas it is not significantly different for individual car. The relationship between the traffic noise level and vehicles speed for car at observational distances (5 and 10 m), and all roughness level indices at 95 % significance level are SPL = 26,49 Log V + 33,015 and SPL = 24,59 Log V + 28,904. For truck with two axles the relationship between the traffic noise level and vehicles speed at observational distances (5 and 10 m) and at 95 % significance level are SPL = 19,06 Log V + 49,464 and SPL = 17,099 Log V + 45,479 for IRI 1,93; SPL = 19,01 Log V + 50,598 and SPL = 18,37 Log V + 43,538 for IRI 2,25; SPL = 17,45 Log V + 53,674 and SPL = 17,60 Log V + 45,426 for IRI = 2,76. For truck with more than two axles the relationship between the traffic noise level and vehicles speed at observational distances (5 and 10 m) and at 95 % significance Ievel are SPL = 28,89 Log V + 35,94 and SPL = 28,20 Log V + 29,23 for IRI 1,93: SPL = 26,84 Log V + 39,75 and SPL = 25,05 Log V + 35,58 for IRI 2,25; SPL = 22,56 Log V + 47,893 and SPL = 23,11 Log V + 38,223 for IRI = 2,76. If the road roughness index increases, the traffic noise resulting from truck with two axles would increase when its speed under 84 km per hour, whereas the traffic noise resulting from truck with more than two axles would increase when its speed under 68 km per hour.